TRANSFORMASI KUALITAS PENDIDIKAN: PERAN DINAS PENDIDIKAN KUANTAN SINGINGI RIAU PERSPEKTIF KI HAJAR DEWANTARA - Fajar Illahi; Gazaligazali; Parqi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the transformation of educational quality and the role of the Education Office of Kuantan Singingi Regency, Riau, in improving the quality of education through the perspective of Ki Hajar Dewantara’s educational thought. The research employed a qualitative approach with a descriptive-analytical design. Data were collected through observation, in-depth interviews, and documentation involving officials of the Education Office, school principals, and teachers. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The findings reveal that the transformation of education in Kuantan Singingi Regency has shown significant progress in terms of educational policy, teacher competency improvement, digitalization of learning, and the enhancement of educational facilities and infrastructure. However, the transformation remains predominantly oriented toward administrative and formalistic aspects, such as academic achievement, graduation rates, and educational bureaucratic targets. The implementation of character education is also still symbolic and has not been fully integrated into the educational culture. In addition, disparities in educational quality between urban and rural areas persist due to limitations in facilities, technological access, and educational resources. From the perspective of Ki Hajar Dewantara, these conditions indicate that education has not been fully directed as a process of humanizing human beings. This study emphasizes that the transformation of educational quality requires a more humanistic, contextual, and culturally grounded paradigm shift. Therefore, the Education Office of Kuantan Singingi Regency needs to integrate the values of exemplary leadership, freedom in learning, empowerment, and character building into educational policies in order to produce students who are not only academically excellent, but also creative, independent, morally grounded, and socially aware.